2014
DOI: 10.1016/j.celrep.2014.01.003
|View full text |Cite
|
Sign up to set email alerts
|

The Cytosolic DNA Sensor cGAS Forms an Oligomeric Complex with DNA and Undergoes Switch-like Conformational Changes in the Activation Loop

Abstract: The presence of DNA in the cytoplasm is a danger signal that triggers immune and inflammatory responses. Cytosolic DNA binds to and activates cyclic GMP-AMP (cGAMP) synthase (cGAS), which produces the second messenger cGAMP. cGAMP binds to the adaptor protein STING and activates a signaling cascade that leads to the production of type-I interferons and other cytokines. Here we report the crystal structures of human cGAS in its apo form, representing its auto-inhibited conformation, as well as cGAMP-bound and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
396
1
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 396 publications
(417 citation statements)
references
References 26 publications
16
396
1
4
Order By: Relevance
“…cGAS binds DNA by interactions with the sugar-phosphate backbone of both DNA strands along a positively charged platform of the protein flanked by a helical spine and a zinc thumb (18)(19)(20). In addition, cGAS has a second positively charged surface interacting with DNA, and crystal structures have revealed that cGAS forms 2:2 complexes with DNA (21,22). AIM2 belongs to the family of PYHIN proteins, consisting of a pyrin domain and one or two may come into contact with DNA sensors in the endosome through uptake via endosomal or autophagy pathways.…”
Section: Recognition Of Dnamentioning
confidence: 99%
“…cGAS binds DNA by interactions with the sugar-phosphate backbone of both DNA strands along a positively charged platform of the protein flanked by a helical spine and a zinc thumb (18)(19)(20). In addition, cGAS has a second positively charged surface interacting with DNA, and crystal structures have revealed that cGAS forms 2:2 complexes with DNA (21,22). AIM2 belongs to the family of PYHIN proteins, consisting of a pyrin domain and one or two may come into contact with DNA sensors in the endosome through uptake via endosomal or autophagy pathways.…”
Section: Recognition Of Dnamentioning
confidence: 99%
“…After binding to cytosolic DNA, cGAS enzymatically generates cyclic dinucleotides (2′3′ cyclic GMP-AMP) that signal via the adaptor molecule stimulator of interferon genes (STING), with the signaling cascade thought to culminate primarily in the production of type I IFN (7,8,14). While cGAS has been demonstrated to affect T cell-independent B cell responses (15), the role of cGAS in driving the humoral response during infection is poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…cGAS is a PRR that senses the presence of cytosolic DNA (7)(8)(9); it is important for initiating the host immune response to intracellular bacteria (10)(11)(12) and DNA viruses (13). After binding to cytosolic DNA, cGAS enzymatically generates cyclic dinucleotides (2′3′ cyclic GMP-AMP) that signal via the adaptor molecule stimulator of interferon genes (STING), with the signaling cascade thought to culminate primarily in the production of type I IFN (7,8,14).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, 3′3′-cGAMP has been found to be produced by certain bacteria (13,14), whereas 2′2′-cGAMP and 3′2′-cGAMP have yet to be found in nature. Recent studies have revealed the molecular basis for the selective formation of the mixed 2′3′-phosphodiester linkages by cGAS (10,(14)(15)(16)(17)(18). However, the function of this linkage isomerism remained unclear and crystallographic studies of the STING/cGAMP complexes provided no insight (9,19).…”
mentioning
confidence: 99%